Christian-Muslim Relations in the Anglican and Lutheran Communions: Historical Encounters and Contemporary Projects
XXVIII, 138 p. 2 illus.
Keywords: Using vignettes of Muslim-Christian engagement within the Anglican and Lutheran communities from around the world, this book provides thoughtful Anglican and Lutheran responses to Muslim-Christian relationships from a variety of perspectives and contexts, lays the groundwork for ongoing faithful, sensitive, and sincere engagement.